DIPG-04. Feasibility and early results of phase 2 open label randomized study of radiotherapy(RT), concomitant nimotuzumab and vinorelbine and re-irradiation at relapse, versus multiple elective radiotherapy courses with concomitant vinorelbine and nimotuzumab for newly diagnosed childhood and adolescence Diffuse intrinsic Pontine Glioma (DIPG). (3rd June 2022) - Massimino, Maura; Biassoni, veronica; Mastronuzzi, Angela; Schiavello, Elisabetta; Barretta, Francesco; Quaglietta, Lucia; Milanaccio, Claudia; Pecori, Emilia; Cacchione, Antonella; Boschetti, Luna; Ruscio, Valentina Di; Chiesa, Silvia; et al.
Abstract: BACKGROUND : The purposes of this trial were to evaluate the feasibility, response, PFS/OS of a randomized study comparing two different RT schedules for DIPG while administering the same systemic treatment. METHODS : Patients: 2-21 years-old with a not-pretreated radiologically verified DIPG (MRI blindly reviewed at diagnosis and every 12 weeks thereafter) and symptoms duration below 6 months. Biopsy was required if suggested by atypical imaging. Vinorelbine 20 mg/m2+nimotuzumab 150 mg/m2 were administered weekly for 12 weeks; thereafter every other week until tumor progression or for up to 2 years. Standard(ST) arm included focal RT at total dose of 54Gy (1.8Gy/day); for local progression re-irradiation was proposed at 19.8Gy, in case of dissemination craniospinal irradiation(CSI) at 36Gy was adopted. Experimental(SP) arm included three elective courses of RT at defined timepoints at 36Gy, 19.8Gy and 19.8Gy with possible reirradiation for relapse at 9 Gy. Incidences of local(L) and distant(D) progression were assessed in a competing risk setting. RESULTS : Aggregated preliminary results are given for 4 Italian centers. 54 pts were screened and 51 included, 27 in ST, 28 males, median age 7 years (range 3-17). Median time of observation was 17.9 months. Twelve patients needed a shunt, 10 during treatment; 20 were biopsied, in 18 cases according local protocols. 19/20 tumors had H3.3 K27 mutation. 41 relapsed, 28 locally, 13 with a component of dissemination. 36 died, one for tracheotomy bleeding. SP irradiation was feasible and never produced significant radionecrosis. Median EFS/OS were 7.3/12.9 months, respectively; EFS/OS at 1 year were 19.0%/57.3%, not differing between patients with local vs. disseminated relapses. Patients submitted to biopsies had more dissemination (P=0.04) and less local progression (P=0.077). CONCLUSIONS : Treatment was feasible and OS confirmed previous results obtained in a single center. Randomization results will be later reported.